The Effect of Peer Group Discussion (PGD)-Based Health Education in the Attitude and Behavior Toward Among Student in Boarding School - Arfa Syukrowardi, Delly; Nuru Alfiah, Siti; Rachmaniah, Dini; Ernawati, Eka (KnE Social Sciences, 2023)
The high incidence of scabies disease in boarding schools is due to the lack of knowledge among Islamic Boarding School Students about scabies prevention. Absence of exposure to health information about scabies is the cause of their lack of knowledge. This study was aimed to determine the effect of peer group discussion (PGD)-based health education on the attitude and behavior toward among students in boarding school in Serang district. This study uses a quasi-experimental design with one group pre and post-test. The intervention in this study was PGD-based health education with two stages, the first was a lecture about scabies prevention, and the second was PGD about how to prevent scabies. A total of 22 respondents were recruited for this study. Questionnaires of attitude and behavior to prevent scabies were used as data collection instruments. Data collection was performed in 3 stages: before the intervention, one hour after the intervention, and two days after the intervention. The mean scores for attitudes before, one hour, and two days after the intervention were 19.86, 22.59, and 25.27 respectively, and the mean scores for behavior before, one hour, and two days after the intervention were 89.23, 96.27, and 106.95 respectively. The result of a one-way within-subject ANOVA test showed that the mean scores of attitudes and behaviors of students were significantly different during one of the time points. This study recommends the school runs a sustainable program of PGD-based health education about scabies to increase awareness of scabies disease prevention among Islamic Boarding School Students. Keywords: student, health education, peer group discussion, scabies, attitude, behavior